2004
DOI: 10.1200/jco.2004.02.110
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the Tissue Inhibitor of Metalloproteinase-1 Protein Is Associated With Progression of Human Non–Small-Cell Lung Cancer

Abstract: These results suggest that TIMP-1, independent of its inhibiting activity of MMPs, may have other function(s) critical for NSCLCs. The significance of our results is two-fold. The adverse outcome in patients with overexpression of TIMP-1 indicates its potential prognostic value in NSCLC. Thus, TIMP-1 overexpression may serve to help identify patients with particularly aggressive disease for adjuvant treatments. In addition, the TIMP-1 molecule may represent a novel therapeutic target for treatment of some NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 48 publications
5
39
0
Order By: Relevance
“…In our study, the TIMP-1 immunoreactive protein appeared as a diffuse staining in the cytoplasm. This is in line with some previous studies using immunohistochemical methods (37,38).…”
Section: Timp-1 In Head and Neck Squamous Cell Carcinomasupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the TIMP-1 immunoreactive protein appeared as a diffuse staining in the cytoplasm. This is in line with some previous studies using immunohistochemical methods (37,38).…”
Section: Timp-1 In Head and Neck Squamous Cell Carcinomasupporting
confidence: 93%
“…Elevated levels of circulating TIMP-1 have previously been shown to be associated with poor prognosis in lung, ovarian, transitional cell or colorectal carcinoma, and tissue TIMP-1 has been reported to predict independently shortened survival in multivariate analysis in breast carcinoma (14, 34 -37). Very recently, Aljada et al also published a study on non -small cell lung cancer showing that patients with a tumor showing a high TIMP-1 expression had an increased risk of death compared with patients presenting with a low expression of TIMP-1 (38).…”
Section: Discussionmentioning
confidence: 99%
“…Although TMA may not be completely representative, it is an efficient way to screen for tissue markers and studies have shown that TMA with 1, 2, and 3 cores will represent about 91%, 96%, and 98%, respectively, compared with whole section studies. [37][38][39][40] Additional full section staining of limited cases showed similar results compared with our microarray results. Compared with our TMA results, the full section results showed no statistical difference in the percentage of positive cases of EAC for IMP3 (TMA, 70%; full section, 77%; Pearson x 2 test, P 5 .86, degrees of freedom of 1) and showed the same mean intensity of expression (mean, 1.27; independent 2-tailed Student t test, P 5 .98) and similar percent of lesional cells with positive staining (TMA mean, 35%; full section mean, 45%; independent 2-tailed Student t test, P 5 .35).…”
Section: Commentsupporting
confidence: 85%
“…Many lines of evidence indicate that TIMP-1 promotes cell proliferation and confers resistance against apoptotic cues (40). However, overexpression of TIMP-1, in general, suppresses cancer progression and metastasis in vivo (17,18), which is also contradictory to the reports that accumulation of TIMP-1 is frequently observed in several types of cancer (19,20) and correlated with poor prognosis (21).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is puzzling to find that TIMP-1 is accumulated in tumor tissues (19,20), and the accumulated TIMP-1 is associated with poor prognosis (21).…”
mentioning
confidence: 99%